Working with Corpora: Increasing Students’ Stylistic Awareness of English Academic Writing - Laily Martin (Universitas Negeri Padang, 2014)
This study attempts to show that working with corpora may help students writing their theses individually and more independently. The objectives are to describe the process of working with own corpora and the benefits by referring to information related to corpus analysis, stylistic analysis, and language awareness, within the context of English academic writing. This study reveals that introducing students to corpus and stylistic analyses helps students to be more aware of academic English commonly used in academic articles with more independent efforts. To gain this, they started the process by choosing their own preferred article source, then collecting, at least, three sample articles related to the field being discussed, and comparing the text structure and the discourse specifically used in the texts. To gather and process texts automatically, they were introduced to Antconc program and, to inspect the language uses in the academic texts manually, they were also introduced to basic stylistic analysis skill. From the study, it can be seen that introducing students to the work and uses of corpora does not only help them write more independently but also make them more attentive and motivated to learn English usages since showing student to works with model writings and allowing them to experiment with the chosen models decrease the writing pressures which are usually caused by the lack of knowledge about various helps to write thesis more effectively.